2016
DOI: 10.1097/md.0000000000005265
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic outcomes of mandibular advancement devices as an initial treatment modality for obstructive sleep apnea

Abstract: Although continuous positive airway pressure (CPAP) is a highly efficacious treatment for obstructive sleep apnea (OSA), there is a need for alternative treatment options, such as sleep surgeries and mandibular advancement devices (MADs), to overcome the limitations of CPAP.This study aimed to analyze the therapeutic outcomes of OSA subjects who were treated with a MAD, and to estimate the clinical impact of MAD as a first-line treatment for OSA.Forty-seven patients diagnosed with OSA received an adjustable MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…This study evaluated the effect of OAs as a first-line treatment in Korean patients with moderate or severe OSA. The cohorts in previous retrospective 9,16,17 and prospective 10 studies only included some patients with moderate OSA (30-60%) or severe OSA (6-57%). One study evaluated the effect of OA treatment in 34 Chinese patients with severe OSA who refused CPAP therapy.…”
Section: Jcnmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated the effect of OAs as a first-line treatment in Korean patients with moderate or severe OSA. The cohorts in previous retrospective 9,16,17 and prospective 10 studies only included some patients with moderate OSA (30-60%) or severe OSA (6-57%). One study evaluated the effect of OA treatment in 34 Chinese patients with severe OSA who refused CPAP therapy.…”
Section: Jcnmentioning
confidence: 99%
“…A few retrospective Korean studies found that the rates of successful OA treatment in patients with moderate OSA and those with severe OSA were 71-82% and 70-75%, respectively. 8,9 One prospective study performed in Thailand included a subset of these patients, and found success rates of 55% and 75% in individuals with moderate OSA and those with severe OSA, respectively. 10 Since the responses to OA treatment vary, careful patient selection is crucial for achieving treatment success in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…A study with drug‐induced sleep endoscopy suggested that oral appliances might not be effective as a first‐line treatment for OSA patients with lateral wall obstruction (Park et al . ). Very recently, in a study run in parallel to our current investigation, tongue base obstruction (rather than palate, pharyngeal lateral walls, or epiglottis) seen on drug‐induced sleep endoscopy was found to increase the probability of a strong oral appliance response (Op De Beeck et al .…”
Section: Introductionmentioning
confidence: 97%
“…For example, in a small study (n = 12), oropharyngeal collapse (based on a multi-tip pharyngeal pressure catheter) was a predictor of oral appliance responses (Ng et al 2006). A study with drug-induced sleep endoscopy suggested that oral appliances might not be effective as a first-line treatment for OSA patients with lateral wall obstruction (Park et al 2016). Very recently, in a study run in parallel to our current investigation, tongue base obstruction (rather than palate, pharyngeal lateral walls, or epiglottis) seen on drug-induced sleep endoscopy was found to increase the probability of a strong oral appliance response (Op De Beeck et al 2018) Intuitively, patients with tongue-related obstruction are expected to exhibit a preferential improvement in collapsibility with mandibular advancement.…”
Section: Introductionmentioning
confidence: 99%
“…Both upper airway narrowing and increased airway resistance reportedly contribute to the underlying pathogenesis of OSA, leading to sleep-related symptoms such as loud snoring, apnea, fatigue, daytime sleepiness and systemic complications if not properly treated [3][4][5][6][7][8] . OSA occurs due to fixed or dynamic upper-airway obstruction caused by anatomical factors or abnormal upper-airway motor tone, and upper-airway obstruction can be caused by collapse at multiple levels, such as the soft palate, uvula, palatine tonsils, lateral pharyngeal walls, and base of the tongue 5,9 . A palatal pattern of collapse is most frequent and numerous surgical techniques have been designed to modify the palate anatomy in OSA patients 10 .…”
mentioning
confidence: 99%